Augmented Buyang Huanwu Decoction facilitates axonal regeneration after peripheral nerve transection through the regulation of inflammatory cytokine production. (5th October 2020) - Kim, Ki-Joong; Hwang, Jinyeon; Park, Ji-Yeun; Namgung, Uk
Abstract: Ethnopharmacological relevance: Herbal formulation Buyang Huanwu Decoction (BYHWD) has been used to treat cardiovascular disorders including cerebral ischemia. Recent studies showed its effects on promoting axonal regeneration after nerve injury. However, compositional reformulation supplemented with herbal components that regulates inflammation may increase its efficacy for nerve repair. Aim of the study: We prepared a new herbal decoction by adding selected herbal components to BYHWD (augmented BYHWD; ABHD) and investigated the effect of ABHD on the production of inflammatory cytokines and axonal regeneration using an animal model of nerve transection and coaptation (NTC). Materials and methods: A rat model of NTC was performed on the sciatic nerve. The sciatic nerve and dorsal root ganglion (DRG) were isolated and used for immunofluorescence staining and western blot analysis. DRG tissue was also used to prepare primary neuron culture and the length of neurites was analyzed. Sensorimotor nerve activities were assessed by rotarod and von Frey tests. Results: Three herbal components that facilitated neurite outgrowth were chosen to formulate ABHD. ABHD administration into the sciatic nerve 1 week or 3 months after NTC facilitated axonal regeneration. Cell division cycle 2 (Cdc2) and brain-derived neurotrophic factor (BDNF) proteins were induced from the reconnected distal portion of the sciatic nerve and the levels were further elevated by in vivo administration of ABHD. Phospho-Erk1/2 level was increased by ABHD treatment as well, implying its role in mediating retrograde transport of BDNF signals into the neuronal cell body. Production of inflammatory cytokines IL-1β and TNF-α was induced in the reconnected nerve but attenuated by ABHD treatment. Behavioral tests revealed that ABHD treatment improved functional recovery of sensorimotor activities. Conclusions: A newly formulated ABHD is effective at regulating the production of inflammatory cytokines and promoting axonal regeneration after nerve transection and may be considered to develop therapeutic strategies for peripheral nerve injury disorders. Graphical abstract: Image 1